Employing a Decision Support System (DSS) application system to modify a non-standard wall-mounting electrical panel using a 3D CAD modelling - Muhammad Arifur Rahman; Sally Cahyati (SINERGI, 2022)
Flexibility in the design process becomes an absolute necessity in a smart factory in the era of industrial manufacturing 4.0. CAD technology with a 3D modeling capability serves as a backbone in the design process in a manufacturing industry. Here, iLogic serving as an add-on of Inventor software will be combined with a Decision Support System (DSS) to build a DSS application system, namely "Panel Auto System". This system will help an engineer modify a 3D model wall-mounting panel to fulfill a non-standard order from his or her customers. This 3D-model database from various parts of the wall-mounting panel is generated from the 3D modeling. Then, by employing the if/then/else rules in the iLogic, the system can modify a 3D model wall-mounting panel data standard and serves as a geometric 3D model based on the customer’s order. The system works well and has been validated. The efficiency of the modeling process using the "Panel Auto System" increases its time efficiency up to 97,6 % compared to a manual process. Therefore, this system can increase the engineer’s productivity in the design of an in-wall mounting panel, and the customers can get the order of their 3D model faster.